Impact of the COVID-19 pandemic on epidemiological and clinical characteristics of Mycoplasma pneumoniae pneumonia in children: a multicenter study from Hubei, China - Du, Hui; Li, Jun; Li, Xilin; Zhao, Junhua; Lu, Wei; Zhang, Qiong; Liu, Wenchun; Luo, Xinbing; Lu, Qiao; Hu, Sanhong; Ma, Jilong; He, Renzhong; et al. (Frontiers in Pediatrics, 2024)
Aims To investigate the epidemiological and clinical characteristics of children with Mycoplasma pneumoniae pneumonia (MPP) in Hubei, China. Methods We retrospectively analyzed inpatients with MPP from 20 hospitals in Hubei, China from January 2021 to December 2022. The co-detected pathogens of Mycoplasma pneumoniae (M. pneumoniae) were investigated using targeted next-generation sequencing (tNGS), and 23S rRNA gene mutations were analyzed to assess the macrolide resistance. Results M. pneumoniae infected 20.7% of patients with CAP, with cough (96.59%) and fever (80.28%) being the most prevalent symptoms. The infection rates in children younger than 1, 1–2, 3–6, 7–12, and older than 12 years were 6.17%, 19.98%, 26.97%, 43.93%, and 2.95%, respectively. Among 1,349 patients undergoing tNGS, the overall co-detection rate was 59.45%, with Streptococcus pneumoniae (29.30%), Haemophilus influenzae (23.57%), and Human rhinovirus (17.21%) being the most commonly co-detected pathogens. In 635 patients undergoing the 23S rRNA gene mutation test, 86.30% exhibited positive mutations (A2063G, 98.00%; A2064G, 1.50%; A2067G, 0.50%). Despite a significant age difference (P = 0.037) between macrolide-resistant M. pneumoniae and macrolide-sensitive M. pneumoniae groups, there were no significant differences in symptoms, lab data, or disease severity. Conclusions In Hubei Province, the prevalence of exhibited consistent changes during the COVID-19 pandemic. MPP was prevalent year-round, particularly in summer and autumn, with school-age children being more susceptible. Co-detections of viruses and bacteria were frequent in MPP cases, and macrolide resistance exceeded 85%. Ongoing surveillance of M. pneumoniae in children is crucial for understanding the healthcare impact of MPP.